A Ressignificação das estruturas da poesia épica em Paradise Lost: o contexto das invocações: The resignification of Epic poetry's structures in Paradise Lost and the context of the invocations - Abreu, Vanessa do Carmo (Rónai – Revista de Estudos Clássicos e Tradutórios, 2016)
Neste trabalho, pretende-se observar a forma como se apresentam no poema Paradise Lost (1674) as estruturas da poesia épica, mais especificamente no que tange ao contexto das invocações. Percebe-se que Milton faz uso das épicas ditas pagãs na construção de um poema épico cristão. O foco deste estudo, pois, é analisar como se dá essa construção, com base na leitura do texto original inglês, na edição de John Leonard (2000) e das edições em português de Lima Leitão (1840) e de Daniel Jonas (2006), esta última bilíngue. Abstract In this work, it is intended to observe the way in which the structures of epic poetry are presented in the poem Paradise Lost (1674), regarding more specifically the context of the invocations. It is noticed that Milton makes use of said pagan epics in the construction of a Christian epic poem. Therefore, the focus of this study is to analyze how is this construction made, based on reading of the original English text, in the John Leonard’s edition (2000) and the Portuguese editions of Lima Leitão (1840) and Daniel Jonas (2006), the latter bilingual. Keywords: invocation; epic poetry; resignification; English epic of the seventeenth century